STRES AKADEMIK PADA MAHASISWA SEMESTER AKHIR DALAM PENYUSUNAN SKRIPSI PADA PRODI PIPS DI INSTITUT PENDIDIKAN INDONESIA GARUT - Ahmad Saepul Irham; Eldi Mulyana; Sudarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore academic stress experienced by final-semester students in completing their undergraduate thesis in the Social Studies Education Program at Institut Pendidikan Indonesia (IPI) Garut. The research is motivated by the increasing number of students experiencing delays in thesis completion due to various academic and non-academic pressures. This study employed a qualitative approach with a phenomenological method to understand students’ subjective experiences. Data were collected through in-depth interviews and observations involving six final-semester students who were in different stages of thesis completion. The results indicate that academic stress manifests in cognitive, emotional, behavioral, and physical forms, such as confusion in determining research direction, emotional instability, procrastination, and physical fatigue. The causes of stress are categorized into internal factors, including decreased motivation and mental exhaustion, and external factors, such as family issues, limited access to supervisors, and difficulties in obtaining references. The impact of academic stress includes decreased learning motivation, delayed thesis completion, and reduced social interaction. To cope with stress, students apply various strategies, including taking breaks, engaging in leisure activities, exercising, and seeking social support from peers, family, and supervisors. This study highlights the importance of effective coping strategies, supportive supervision, and institutional support in reducing academic stress among final-year students.